Pentingnya Pemahaman Logika dalam Berpikir kiritis - Patrisius Liber; Loris Loris; Joni Joni; Mozes Lawalata (Institut Nalanda, 2024)
The purpose of this studay is to know how important understanding logic is in critical thingking. Logic teaches us how a person can think precisely and ordely. As a human being, he should have the abilitiy to think to obtain and know all scientific information. Every human being is given reason to be able to remember, respond, argue, think and know new things. In today’s modern era, the importance of understanding logic in critical thinking is very important in making the right decision to take action. Critical thinking include logical thingking and use of reasoning, includes the skills to compare, analyze, classify, do, relate, cause and effect, describe thinking patterns, make analogies, arrange series, give reasons deductively and inductively, critical thinking includes includes determining the meaning and importance of what is seen or stated in the assessment of arguments, considering conclusions drawn based on supporting evidence which is valid and adequate. Critical thinking is a deep thinking activity that connects various kinds of reasoning principles, critical thinking as an ability needed to acquire knowledge.